2020
DOI: 10.1111/jcmm.15885
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated HDAC3 elevates microRNA‐495‐3p to restrain epithelial‐mesenchymal transition and oncogenicity of melanoma cells via reducing TRAF5

Abstract: MicroRNAs (miRNAs) are emerging biomarkers in biological processes and the role of miR‐495‐3p has been identified in melanoma, while the detailed molecular mechanisms remain to be further explored. We aim to explore the effect of histone deacetylase 3 (HDAC3) and miR‐495‐3p on epithelial‐mesenchymal transition (EMT) and oncogenicity of melanoma cells by regulating tumour necrosis factor receptor‐associated factor 5 (TRAF5). Levels of HDAC3, miR‐495‐3p and TRAF5 in melanoma tissues and pigmented nevus tissues w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…As the regulatory gene with the smallest hazard ratio (HR) (0.732) in our study, TAR5 has been studied in many cancers. Previous studies have demonstrated that TAR5 is a key target to inhibit tumor cell migration or proliferation, and the expression of TRAF negatively correlates with prognosis [25][26][27]. However, in this study, we obtained the opposed conclusion that TAR5 is a protective factor for HNSCC, and TAR5 expression contributed to a longer OS time.…”
Section: Discussioncontrasting
confidence: 75%
“…As the regulatory gene with the smallest hazard ratio (HR) (0.732) in our study, TAR5 has been studied in many cancers. Previous studies have demonstrated that TAR5 is a key target to inhibit tumor cell migration or proliferation, and the expression of TRAF negatively correlates with prognosis [25][26][27]. However, in this study, we obtained the opposed conclusion that TAR5 is a protective factor for HNSCC, and TAR5 expression contributed to a longer OS time.…”
Section: Discussioncontrasting
confidence: 75%
“…Although miR expression profile in metaplastic breast cancer is poorly studied, as most studies pool them within the TNBC group, another miR family, which is downregulated in most TNBC, including metaplastic, is the miR-200 family [81,82]. In gastric carcinoma and melanoma, miR-495-3p is down-regulated and associated with poor disease prognosis [83,84]. Although no reports have studied miR-495-3p expression exclusively in metaplastic breast cancer, it is important to note that miR-200a targets FOXC1 [85], which is upregulated in metaplastic breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant, other microRNAs we identified are involved in the EMT process. For example, hsa-miR-145-3p, hsa-miR-324-5p and hsa-miR142-5p act as inhibitors of EMT in different cell types [81][82][83][84]; on the contrary, high expression and activation of hsa-miR 483-3p, hsa-miR-128-3p are involved in EMT induction [85,86].…”
Section: Discussionmentioning
confidence: 99%